2017
DOI: 10.5194/acp-2017-8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delivery of halogenated very short-lived substances from the West Indian Ocean to the stratosphere during Asian summer monsoon

Abstract: <p><strong>Abstract.</strong> Halogenated very short-lived substances (VSLS) are naturally produced in the ocean and emitted to the atmosphere. When transported to the stratosphere, these compounds can have a significant influence on the ozone layer and climate. During a research cruise on RV <i>Sonne</i> in the subtropical and tropical West Indian Ocean in July and August 2014, we measured the VSLS, methyl iodide (CH<sub>3&… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 35 publications
5
26
0
Order By: Relevance
“…The new inventory in this work also shows high oceanic CH 2 Br 2 fluxes over the Indian Ocean and South China Sea (0.6–0.9 × 10 7 molecules·cm −2 ·s −1 ), very close to that reported over the South China Sea (0.7 ± 0.6 × 10 7 molecules·cm −2 ·s −1 ; Fuhlbrügge et al, ), but is a factor of ~2 lower than that reported over the Indian Ocean (1.6 ± 3.3 × 10 7 molecules·cm −2 ·s −1 ; Fiehn et al, ). The Ordóñez‐2012 inventory shows less than 0.5 × 10 7 molecules·cm −2 ·s −1 in the entire region, lower than that reported in Fuhlbrügge et al () or Fiehn et al (). More surface seawater observations in this region will certainly improve the performance of the machine‐learning emulator, as well as the bottom‐up oceanic emission inventory for CHBr 3 and CH 2 Br 2 .…”
Section: Comparison Of the Global Oceanic Emissionssupporting
confidence: 79%
See 2 more Smart Citations
“…The new inventory in this work also shows high oceanic CH 2 Br 2 fluxes over the Indian Ocean and South China Sea (0.6–0.9 × 10 7 molecules·cm −2 ·s −1 ), very close to that reported over the South China Sea (0.7 ± 0.6 × 10 7 molecules·cm −2 ·s −1 ; Fuhlbrügge et al, ), but is a factor of ~2 lower than that reported over the Indian Ocean (1.6 ± 3.3 × 10 7 molecules·cm −2 ·s −1 ; Fiehn et al, ). The Ordóñez‐2012 inventory shows less than 0.5 × 10 7 molecules·cm −2 ·s −1 in the entire region, lower than that reported in Fuhlbrügge et al () or Fiehn et al (). More surface seawater observations in this region will certainly improve the performance of the machine‐learning emulator, as well as the bottom‐up oceanic emission inventory for CHBr 3 and CH 2 Br 2 .…”
Section: Comparison Of the Global Oceanic Emissionssupporting
confidence: 79%
“…The Ordóñez‐2012 inventory also has fixed values in the subtropical, midlatitude, and high‐latitude oceans. We noted that the new bottom‐up oceanic emission inventory of CHBr 3 shows high sea‐to‐air flux over the Indian Ocean, South China Sea, and Java Sea (2–3 × 10 7 molecules·cm −2 ·s −1 ), which is comparable to the oceanic CHBr 3 flux reported over the South China Sea (2.5 ± 2.9 × 10 7 molecules·cm −2 ·s −1 ; Fuhlbrügge et al, ), but toward the upper end of that over the Indian Ocean (1.5 ± 2.0 × 10 7 molecules·cm −2 ·s −1 ; Fiehn et al, ). The Ordóñez‐2012 inventory, however, shows approximately 1.5–2.0 × 10 7 molecules·cm −2 ·s −1 , in this region, comparable to that reported in Fiehn et al (), but is toward the lower end of that in Fuhlbrügge et al ().…”
Section: Comparison Of the Global Oceanic Emissionssupporting
confidence: 65%
See 1 more Smart Citation
“…These coupled interactions transport energy away from convective regions, which tend to be anchored over the warmest SSTs, into subsidence-dominated regions where SSTs are usually cooler. Associated tracer transports have extensive influences on humidity, ozone, and other constituents in the upper troposphere (Folkins et al, 2002;Jiang et al, 2007;Fiehn et al, 2017;Pan et al, 2017), while momentum transport, latent heat release, and radiative effects modulate circulation patterns in both the troposphere and stratosphere (LeMone et al, 1984;Carr and Bretherton, 2001; Lane and Moncrieff, 2008;Geller et al, 2016;Kim et al, 2017). Changes in precipitation are governed to leading order by the balance of changes in radiative cooling and condensational heating in the atmosphere (O'Gorman et al, 2011), both of which are intimately connected with the distribution and properties of high clouds.…”
Section: Introductionmentioning
confidence: 99%
“…Then from the upper troposphere air may be taken up into the tropical stratosphere via the large‐scale upwelling circulation, or alternatively be transported laterally into the extratropical lower stratosphere through disturbances to the subtropical jet that depend on the time variation of the anticyclone itself. Thus the lower and upper parts of the monsoon combine to form a potentially rapid pathway for chemical species and aerosols originating from anthropogenic emissions at the surface in the south and east Asian regions to reach the stratosphere, with implications for climate and for ozone, since the chemical species include short‐lived halogen species (Park et al ., ; Randel et al, ; Bourassa et al, ; Fiehn et al, ).…”
Section: Introductionmentioning
confidence: 99%